Phenolic compounds and antioxidant capacity in different-colored and non-pigmented berries of bilberry (Vaccinium myrtillus L.). (December 2017) - Colak, Nesrin; Primetta, Anja K.; Riihinen, Kaisu R.; Jaakola, Laura; Grúz, Jiři; Strnad, Miroslav; Torun, Hülya; Ayaz, Faik Ahmet
Abstract: Bilberries and their products are popular worldwide and represent a very interesting source of dietary antioxidants. Berries of eight different-colored and non-pigmented bilberry ( Vaccinium myrtillus L.) samples from Finland were evaluated in terms of antioxidant capacity and total phenolic compounds (range, 220.06 – 3715.21 mg/100 g dw) and total monomeric anthocyanin (range, 206.18 – 867.52 mg/100 g dw) contents. Delphinidin (range, 5915.93–18108.39 µg /g dw) was the major anthocyanin moiety, while sinapic acid was the major phenolic acid in the free form (range, 0.01 – 6.06 μg /g dw), and p -coumaric acid in the ester (range, 26.39 – 110.78 µg /g dw), glycoside (range, 15.83 – 57.73 μg /g dw) and ester-bound (range, 2.32 – 14.20 μg /g dw) forms. The white colored berry samples did not contain any anthocyanins, but the colored berries did contain them. Antioxidant capacity was much higher in colored (pink to blue/black) berry samples than in the white sample, and it was more related to the total phenolic concentration rather than to the anthocyanin concentration. This is the first time that these different-colored berry phenotypes of bilberry ( V. myrtillus L.) have been analyzed within the same study. Highlights: Phenolics in wild-type colored and non-colored berries of Finnish bilberries. Noticeable difference in phenolics acid forms was found among the berries. Syringic, ferulic, 4-coumaric and sinapic acids significantly differed among the berries. The main anthocyanidin was delphinidin in the wild-type berries. The wild-type berry samples have higher antioxidant capacity than non-colored.